A Mexican strategy to promote greater ethics in academic communications through nation-wide access to Turnitin - Cortes Vera, Jose de Jesus (2018)
This document explores the challenges and perspectives behind the initiative for enabling Mexican universities and research centers to access the Turnitin software, a strategy for promoting greater ethics in academic and scientific communications. It presents information obtained through documentary research, from the experience of using the software during the last academic semester, from interviews with the coordinator of the National Consortium of Scientific and Technological Resources (CONRICyT), and with the Turnitin company representative for Mexico. Given the emerging nature of this project and the complexity of the issue, the results presented consist of a non-comprehensive list of benefits and challenges that emerged from using the software, as well as recommendations to harness its use and consolidate a culture for the ethical use of information in academic and scientific communications.